Engineering Behaviour of Fibre-Reinforced Pond Ash and Silty Sand. Issue 6 (1st January 1999) - Kanaujia, V.K.; Chandra, D.; Kumar, R.
Abstract : This note presents the results of laboratory investigations conducted on silty sand and pond ash specimens reinforced with randomly distributed polyester fibres. The test results reveal that the inclusion of fibres in soils increases the peak compressive strength, CBR value, peak friction angle, and ductility of the specimens. It is concluded that the optimum fibre content for both silty sand and pond ash is approximately 0.3 to 0.4% of the dry unit weight.